1993
DOI: 10.1037/0022-006x.61.1.104
|View full text |Cite
|
Sign up to set email alerts
|

African-American adolescents' knowledge, health-related attitudes, sexual behavior, and contraceptive decisions: Implications for the prevention of adolescent HIV infection.

Abstract: African-American adolescents (N = 195) completed measures of knowledge related to acquired immunodeficiency syndrome (AIDS), attitudes toward condoms, health locus of control, vulnerability to human immunodeficiency virus (HIV) infection, peer sexual norms, personal sexual behavior for the past 6 months, and contraceptive preferences. Hotelling's T2 tests revealed that girls were more knowledgeable about AIDS, reported fewer sexual partners, held more positive attitudes toward precautionary sexual behavior, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
43
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(49 citation statements)
references
References 41 publications
5
43
0
Order By: Relevance
“…Research suggests contextual factors such as political unrest, violence and economic conditions can influence sexual risk [1012]. Youth may be particularly vulnerable to having STIs due to heightened sexual curiosity [13]. One study examining individual psychosocial predictors of risky behavior in young people found that impulsive propensity, the tendency to act without forethought, was associated with sexual risk behavior [14].…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests contextual factors such as political unrest, violence and economic conditions can influence sexual risk [1012]. Youth may be particularly vulnerable to having STIs due to heightened sexual curiosity [13]. One study examining individual psychosocial predictors of risky behavior in young people found that impulsive propensity, the tendency to act without forethought, was associated with sexual risk behavior [14].…”
Section: Introductionmentioning
confidence: 99%
“…11 Among sexually experienced youth, findings suggest that greater HIV knowledge is associated with more consistent condom use and greater likelihood of HIV testing. 12,13,14 However, other studies have either failed to replicate this relationship or have found that more knowledge is associated with greater risk-taking. 15,16,17 …”
mentioning
confidence: 99%
“…They also frequently experiment with drugs during this time, which may impair their cognition, increasing the chance that they will engage in risky sexual behaviors (Rotheram-Borus et al, 2000). Furthermore, adolescence is a time of high sexual activities and often unprotected sex (Lawrence, 1993).…”
mentioning
confidence: 99%